Um estudo sobre o conhecimento adquirido pelos alunos da graduação numa disciplina com conteúdo de matemática do ensino médio - Gonçalves, Tatiana Ribeiro Mustafa (Universidade Federal de São Carlos, 2020)
The subject studied in this dissertation is part of "Teaching Mathematics". We analyzed, with tests throughout the course "Real Numbers and Functions", the knowledge of 45 students of some Mathematics topics that are part of high school. It is presented Numerical data regarding the correctness and error of the proposed exercises, model tests (well written and with the most correctness), solutions with the most common errors and analysis of such errors.
A study about the knowledge obtained by undergraduate students in a course with high school mathematics content
Keywords: Análise de erros; Conteúdo de matemática do ensino médio; Disciplina da graduação; Error analysis; High school mathematics content; Undergraduate course; CIENCIAS EXATAS E DA TERRA::MATEMATICA